The angiosome concept in revascularization of the shin and foot arteries in patients with diabetes mellitus - Yu. M. Gupalo; D. Yu. Shapovalov; V. V. Shaprynskyi; O. F. Dzygal; A. V. Shamray-Sas; A. M. Kucyn (Клінічна хірургія)
Objective. To analyze the results of revascularization of the shin and foot arteries in patients with diabetes mellitus in accordance to the angiosome concept.